Extrapolating Prognostic Factors of Primary Curative Resection to Postresection Recurrences Hepatocellular Carcinoma Treatable by Radiofrequency Ablation - Hui Ma; Zhongchen Li; Jia Yuan; Lan Zhang; Xiaoying Xie; Xin Yin; Rongxin Chen; Zhenggang Ren (Gastroenterology Research and Practice)
Objective. Recurrence after curative resection for hepatocellular carcinoma (HCC) is a major cause of death from this disease. Factors of primary curative resection are available and potential in the prognosis of follow-up treatment. Our aim was to assess the prognostic significance of primary curative resection factors in recurrent HCC patients undergoing radiofrequency ablation therapy (RFA). Methods. In this retrospective study, we assessed 235 patients who underwent limited RFA of HCC recurrences (tumors≤5 cm; nodules≤3) after primary curative resection. Factors of primary curative resection were collected, and overall survival and recurrence-free survival were evaluated by the Kaplan-Meier method. Univariate and multivariate analyses were used to identify significant prognostic factors. Results. After a median follow-up of 36 months, 54 patients died, and 128 patients had hepatic recurrence. On univariate analyses, patients whose primary tumors were less differentiated (p=0.032 and p=0.048) and required less time to recur (p=0.013 and p=0.001) after curative resection displayed poorer overall survival and higher recurrence rates following RFA. On multivariate analyses, the pathologic tumor grade (p=0.026 and p=0.038) and recurrence-free survival after primary curative resection (p=0.028 and p<0.001) emerged as independent risk factors of survival and HCC recurrence. Conclusions. Primary tumor differentiation and time to recurrence after curative resection are viable prognostic factors of overall survival and further recurrence risk in patients undergoing RFA of recurrent HCC.